Large-particle recycled aggregate concrete and preparation method thereof

Through the synergistic effect of modified fibers and microsphere fillers, combined with spraying treatment and thermally expanded microspheres, the problems of low density and poor permeability of large-grain regenerated aggregate concrete are solved, and the permeability and durability of concrete are significantly improved. Reduces environmental pollution and energy consumption.

CN119263731APending Publication Date: 2025-01-07青岛建一混凝土有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411387104.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional large-grain recycled aggregate concrete has low density, poor permeability and reduced durability due to impurities and irregular particle shapes. The existing reinforcement treatment methods have problems such as environmental pollution, high energy consumption and high economic costs.

Method used

Modified fiber filler and modified microsphere filler are used to fill the internal pores of concrete through the synergistic effect of fiber network structure and microspheres, reducing interface defects, improving density and impermeability, and passing through ethyl cellulose and phosphatidylserine Spraying enhances fiber bonding, and combines thermally expanded microspheres and ceramic microspheres to enhance crack resistance.

Benefits of technology

It significantly improves the permeability and durability of concrete, reduces moisture permeability path, enhances the stability of the fiber network structure, reduces the formation of cracks and pores, realizes efficient utilization of recycled aggregates, reduces environmental pollution and energy Consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071190200000101
    Figure BDA0005071190200000101
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses large-particle recycled aggregate concrete and a preparation method thereof. The large-particle recycled aggregate concrete is prepared from the following components in parts by weight: 700 to 950 parts of recycled coarse aggregate, 500 to 650 parts of fine aggregate, 300 to 400 parts of cement, 40 to 60 parts of fly ash, 40 to 60 parts of mineral powder, 60 to 80 parts of self-repairing filler, 20 to 30 parts of water reducing agent, 3 to 8 parts of silane coupling agent, 60 to 80 parts of floating bead and 150 to 250 parts of water, the self-repairing filler comprises a modified fiber filler and a modified microsphere filler in a mass ratio of (1-4): (2-6). The large-particle recycled aggregate concrete prepared by the preparation method disclosed by the invention has excellent impermeability and crack resistance and relatively good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and more specifically, to a large-particle recycled aggregate concrete and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization, the amount of construction waste is increasing year by year, and the recycling of waste concrete has become an important issue. In order to alleviate the environmental problems and natural resource shortage caused by the increasing amount of solid waste from building demolition and the demand for sand and gravel resources, researchers use recycled coarse aggregate obtained from waste concrete to replace natural coarse aggregate to prepare concrete.

[0003] The impermeability of traditional concrete mainly depends on its density. Large-particle recycled aggregates often contain more impurities and irregular particle shapes due to differences in their sources and processing techniques. These impurities and irregular shapes will cause more infiltration channels inside the concrete made of recycled aggregates, affecting the density of the concrete, thereby causing a decrease in the mechanical properties of the concrete, a decrease in its impermeability and a decrease in its durability.

[0004] In view of the above-mentioned related technologies, the inventors found that in order to improve the mechanical properties and impermeability of concrete prepared with large-particle recycled aggregates and improve the utilization rate of large-particle recycled aggregates, the strengthening treatment methods in the prior art are roughly divided into two categories. One is to remove mortar by physical and chemical methods, including multiple crushing, repeated ball milling particle shaping, high-temperature calcination followed by ball milling, microwave heating followed by grinding, ultrasonic vibration and other physical methods, and acid solution immersion, washing and immersion chemical methods; the second is to strengthen the surface treatment of recycled coarse aggregates, such as the use of PO42.5 cement with volcanic ash effect, silica fume, fly ash, nano-silicon dioxide solution immersion method, etc. The above treatment methods all have a certain improvement on the mechanical properties and impermeability of recycled aggregates, but the disadvantage is that the strong acid solution and other waste liquids and waste slurries used in the strengthening treatment process will cause environmental pollution; the use of machine crushing, grinding and high-temperature calcination requires a lot of energy consumption, increases carbon emissions, and increases economic and time costs. Summary of the invention

[0005] In order to improve the impermeability of concrete prepared with large-particle recycled aggregate, the present application provides a large-particle recycled aggregate concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a large-particle recycled aggregate concrete, which adopts the following technical solution: A large-particle recycled aggregate concrete comprises the following raw materials, measured in parts by weight: 700-950 parts of recycled coarse aggregate, 500-650 parts of fine aggregate, 300-400 parts of cement, 40-60 parts of fly ash, 40-60 parts of mineral powder, 60-80 parts of self-repairing filler, 20-30 parts of water reducer, 3-8 parts of silane coupling agent, 60-80 parts of floating beads and 150-250 parts of water; The self-repairing filler comprises a modified fiber filler and a modified microsphere filler in a mass ratio of (1-4):(2-6).

[0007] By adopting the above technical solution, the addition of recycled coarse aggregate realizes the reuse of waste concrete and can alleviate the problem of shortage of natural resources.

[0008] The self-repairing filler is composed of modified fiber filler and modified microsphere filler, which can make up for the performance of concrete made of recycled aggregate. The modified fiber filler and modified microsphere filler can promote the formation of aggregate interlocking effect of recycled coarse aggregate inside the raw material, fill the pores and microcracks generated by the crushing and screening of waste concrete, reduce the porosity of concrete, improve the interface transition zone between recycled aggregate and cement paste, reduce interface pores and defects, and significantly improve the overall impermeability of concrete. Microspheres have high water absorption and can absorb excess water in concrete, reduce water migration, and further improve the impermeability of concrete.

[0009] The modified fiber filler and modified microsphere filler work together to further fill the pores between the two, which helps to improve the density of concrete, make the structure of concrete denser, and reduce the possibility of penetration. In addition, the addition of fibers and microspheres can improve the toughness and crack resistance of concrete, reduce the occurrence of cracks, and improve the durability of concrete.

[0010] Optionally, the modified fiber filler comprises basalt fiber and polyvinyl alcohol fiber in a mass ratio of (2-8):(1-4).

[0011] By adopting the above technical solution, basalt fiber is a rigid fiber, and the mixture of the two can form a stable fiber network structure inside the concrete. On the one hand, it can produce a strong bonding force with the concrete matrix, improve the overall density of the concrete, thereby reducing cracks and pores. On the other hand, the rigid fiber can significantly improve the crack resistance of the concrete, reduce the formation of cracks, and improve the durability of the concrete.

[0012] Polyvinyl alcohol fiber is a flexible fiber with better toughness, which can better fill the tiny pores in concrete, reduce the penetration path of water, and improve the impermeability. In addition, the flexibility of polyvinyl alcohol fiber helps to absorb and disperse stress and improve the toughness of concrete.

[0013] The synergistic use of basalt fiber and polyvinyl alcohol fiber can combine the advantages of both. The flexibility of the flexible fiber can adapt to the pores of the fiber network structure, provide expansion space for the hydration of cement materials, reduce expansion stress, and make the concrete less likely to crack and hollow. The strength and flexibility of the rigid-flexible fiber can be used during shrinkage to avoid cracks caused by shrinkage, improve the durability of the concrete, and further enhance the concrete's impermeability.

[0014] Optionally, the method for preparing the modified fiber filler comprises the following steps: The basalt fiber and the polyvinyl alcohol fiber are mixed in proportion to obtain mixed fibers; The ethyl cellulose solution is evenly sprayed on the surface of the mixed fiber, and then the phosphatidylserine solution is evenly sprayed, and the mixture is dried and dispersed until the basalt polyvinyl alcohol fibers are not adhered to each other.

[0015] By adopting the above technical solution, ethyl cellulose is a water-soluble polymer that can improve the surface activity of the fiber and enhance the contact area and bonding force between it and the concrete matrix. Phosphatidylserine solution is a lipid containing a phosphate group that can form chemical bonds with metal ions in concrete, enhance the chemical bonding between the fiber and the matrix, and make the fiber network structure formed by basalt fiber and polyvinyl alcohol fiber in concrete more stable.

[0016] The spraying treatment can form a protective film on the fiber surface, which can fill the tiny gaps between the fiber and the concrete matrix, reduce the defects in the interface transition zone, reduce the penetration of water and air, and enhance the concrete's impermeability and crack resistance.

[0017] The spraying treatment of ethyl cellulose and phosphatidylserine solution strengthens the bonding between the fiber and the concrete matrix and improves the crack resistance of the concrete.

[0018] Optionally, the modified microsphere filler includes thermal expansion microspheres and ceramic microspheres in a mass ratio of (2-5):1.

[0019] By adopting the above technical solution, the thermal expansion microspheres can expand under temperature changes, which helps the self-repair of concrete and can fill the pores and cracks in the recycled aggregate. Ceramic microspheres have high hardness and wear resistance, which improves the mechanical strength of concrete, reduces the cracks in concrete when encountering external forces, and improves the durability of concrete. The two are used in conjunction with the fiber network structure formed by the modified fiber filler, which is evenly distributed in the concrete and can effectively improve the impermeability of concrete.

[0020] Optionally, the method for preparing the modified microsphere filler comprises the following steps: Heat paraffin to 60-70°C, stir at 400-500r / min for 30-60min, add heat-expandable microspheres and ceramic microspheres, stir at 800-900r / min at 60-70°C for 20-30min, cool to room temperature and crush to obtain the product; the amount of paraffin added is 30-40% of the heat-expandable microspheres.

[0021] By adopting the above technical solution, the fluidity of the heat-expandable microspheres themselves is poor, and paraffin has the characteristic of rapidly decreasing viscosity after heating. Wrapping paraffin on the surface of the heat-expandable microspheres during the preparation process can effectively enhance the fluidity and adhesion of the heat-expandable microspheres and quickly fill the pores and cracks in the concrete.

[0022] In addition, paraffin is hydrophobic and can effectively reduce moisture migration in concrete, reduce the diffusion rate of moisture in concrete, and improve impermeability. Paraffin will expand when heated. This expansion effect can promote the movement of microspheres in concrete, promote the filling of microspheres in the pores in concrete, and further improve impermeability.

[0023] Optionally, the recycled coarse aggregate is 10-20 mm continuously graded coarse aggregate obtained after crushing and screening of waste concrete, and its crushing value is 12-20%; the fine aggregate is sand with a fineness modulus of 2.6-3.2; the fly ash is Class F Grade I fly ash, and the mineral powder is Grade S95 mineral powder.

[0024] Optionally, the water reducing agent is a polycarboxylic acid-based water reducing agent.

[0025] By adopting the above technical solution, polycarboxylate water reducer can significantly reduce the water-cement ratio of concrete, which means that the amount of water used in concrete is reduced under the same amount of cement. The reduction of water-cement ratio means that less water is used in concrete, thereby reducing the number of capillary pores in cement paste, and also helps to reduce the shrinkage and cracking of concrete during the hardening process, thereby reducing the penetration path and improving the impermeability of concrete.

[0026] Optionally, the floating beads have an apparent density of 0.6×10 3 kg / m 3 -0.8×10 3 kg / m 3 Fly ash spherical floating beads.

[0027] In a second aspect, the present application provides a method for preparing large-particle recycled aggregate concrete, using the following technical solution: A method for preparing large-particle recycled aggregate concrete comprises the following steps: The recycled coarse aggregate, fine aggregate, cement, fly ash and floating beads are mixed to prepare a primary mixture; The modified microsphere filler and the modified fiber filler are mixed to prepare the self-repairing filler; Add the primary mixture into water, add the silane coupling agent, add the modified microsphere filler after mixing, and stir to obtain the product.

[0028] By adopting the above technical scheme, the preparation method of the present application is simple to operate and easy to realize industrialization. The modified microsphere filler is added at the end to reduce the damage to the modified microsphere filler in the early mixing process, thereby ensuring its functional effectiveness in concrete.

[0029] In summary, this application has the following beneficial effects: 1. Modified fiber fillers and modified microsphere fillers are added to the concrete of the present application. Through the mutual complementation between fibers and microspheres, the recycled coarse aggregate can be effectively promoted to form an aggregate locking effect inside the concrete, effectively fill the pores and defects inside the concrete, improve the compactness inside the concrete, make up for the defects of the recycled aggregate, and improve the impermeability of the concrete.

[0030] 2. In this application, basalt fiber and polyvinyl alcohol fiber are preferably used. The rigid fiber and flexible fiber complement each other, combined with the flexibility of the flexible fiber and the crack resistance of the rigid fiber, so that the fiber can more completely supplement the internal pores of the concrete, effectively prevent cracks and hollowing in the concrete, and effectively reduce the path for moisture and air to enter the concrete.

[0031] 3. The present application uses paraffin to wrap the heat-expandable microspheres and ceramic microspheres, which can effectively improve the fluidity and adhesion of the microspheres inside the concrete, and help to quickly fill the pores and cracks in the concrete prepared from recycled aggregates. DETAILED DESCRIPTION

[0032] The following examples further illustrate the present application in detail.

[0033] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Recycled coarse aggregate is 10-20mm continuous graded coarse aggregate after the waste concrete is crushed and screened, and the crushing value is 12-20%; Cement, ordinary silicate P.O42.5 cement is selected; Fine aggregate should be sand with a fineness modulus of 2.6-3.2; The fly ash is selected from Class F Grade I fly ash; The mineral powder is S95 grade mineral powder; Basalt fiber, selected from Taian Anfeng New Material Technology Co., Ltd., model AF53; Polyvinyl alcohol fiber, selected from Tai'an Anfeng New Material Technology Co., Ltd., the core material used is polyester fiber; Thermal expansion microspheres, selected from Beijing Yijin Technology Co., Ltd., with a particle size of 5-100 μm; Ceramic microspheres, selected from Shanghai Gerunya Nanomaterials Co., Ltd., with a particle size of 0.2-40 μm; The ethyl cellulose solution is a 1% by mass ethyl cellulose ethanol solution, and the ethanol is anhydrous ethanol with a mass fraction of 99%; the ethyl cellulose is selected from Wuhan Jushun Chemical Co., Ltd., 9004-57-3; Phosphatidylserine, selected from Tai'an Jiangzhou Biotechnology Co., Ltd., 51446-62-9; Terpene resin, selected from Guangdong Chino, TA series terpene resin; Silane coupling agent, choose Momentive silane coupling agent MP200; The water reducer is selected from Langfang Shenqi Energy Saving Technology Co., Ltd., a high-performance polycarboxylate water reducer with model D0001.

[0034] Modified fiber filler preparation examples 1.1-1.6 Preparation Example 1.1 The modified fiber filler comprises basalt fiber and polyvinyl alcohol fiber in a mass ratio of 2:1, and the preparation method thereof comprises the following steps: S1: mixing the basalt fiber and the polyvinyl alcohol fiber uniformly to obtain mixed fiber; S2: Ethyl cellulose solution is uniformly sprayed on the surface of the mixed fiber, and then phosphatidylserine solution is uniformly sprayed, and the mixture is dried and dispersed until there is no mutual adhesion between the basalt fiber and the polyvinyl alcohol fiber. The phosphatidylserine solution is obtained by mixing phosphatidylserine, terpene resin and petroleum ether in a mass ratio of 1:0.2:90.

[0035] Preparation Example 1.2 The modified fiber filler is different from Preparation Example 1.1 in that the mass ratio of basalt fiber to polyvinyl alcohol fiber is 5:4, and the other steps are the same as Preparation Example 1.1.

[0036] Preparation Example 1.3 The modified fiber filler is different from Preparation Example 1.1 in that the mass ratio of basalt fiber to polyvinyl alcohol fiber is 8:3, and the other steps are the same as Preparation Example 1.1.

[0037] Preparation Example 1.4 The modified fiber filler comprises basalt fiber and polyvinyl alcohol fiber in a mass ratio of 2:1. The preparation method thereof comprises the following steps: the basalt fiber and the polyvinyl alcohol fiber are mixed uniformly to obtain the modified fiber filler.

[0038] Preparation Example 1.5 The modified fiber filler is different from that of Preparation Example 1.1 in that polyvinyl alcohol fiber is not added. The preparation method thereof comprises the following steps: uniformly spraying an ethyl cellulose solution on the surface of the basalt fiber, and then uniformly spraying a phosphatidylserine solution, and drying and dispersing the basalt fibers until there is no mutual adhesion between the fibers. The phosphatidylserine solution is prepared by mixing phosphatidylserine, terpene resin and petroleum ether in a mass ratio of 1:0.2:90.

[0039] Preparation Example 1.6 The modified fiber filler is different from that of Preparation Example 1.1 in that basalt fiber is not added. The preparation method thereof comprises the following steps: uniformly spraying an ethyl cellulose solution on the surface of a polyvinyl alcohol fiber, and then uniformly spraying a phosphatidylserine solution, and drying and dispersing the phosphatidylserine solution until the polyvinyl alcohol fibers are not adhered to each other, thereby obtaining a phosphatidylserine solution prepared by mixing phosphatidylserine, terpene resin and petroleum ether in a mass ratio of 1:0.2:90.

[0040] Modified microsphere filler preparation examples 2.1-2.6 Preparation Example 2.1 The modified microsphere filler comprises heat-expandable microspheres and ceramic microspheres in a mass ratio of 2:1. The preparation method thereof comprises the following steps: heating paraffin to 60°C, stirring at 400 r / min for 60 min, adding the heat-expandable microspheres and ceramic microspheres, stirring at 800 r / min at 70°C for 20 min, cooling to room temperature, and crushing to obtain the modified microsphere filler; the amount of the paraffin added is 30% of the total mass of the heat-expandable microspheres and ceramic microspheres.

[0041] Preparation Example 2.2 The modified microsphere filler comprises heat-expandable microspheres and ceramic microspheres in a mass ratio of 3:1. The preparation method thereof comprises the following steps: heating paraffin wax to 70°C, stirring at 500 r / min for 30 min, adding the heat-expandable microspheres and ceramic microspheres, stirring at 900 r / min at 60°C for 30 min, cooling to room temperature, and crushing to obtain the modified microsphere filler; the amount of the paraffin wax added is 40% of the total mass of the heat-expandable microspheres and ceramic microspheres.

[0042] Preparation Example 2.3 The modified microsphere filler is different from Preparation Example 2.1 in that the mass ratio of heat-expandable microspheres to ceramic microspheres is 5:1, and the other steps are the same as Preparation Example 2.1.

[0043] Preparation Example 2.4 The modified microsphere filler comprises heat-expandable microspheres and ceramic microspheres in a mass ratio of 2:1. The preparation method thereof comprises the following steps: the heat-expandable microspheres and the ceramic microspheres are uniformly mixed to obtain the modified microsphere filler.

[0044] Preparation Example 2.5 The modified microsphere filler is different from the preparation example 2.1 in that ceramic microspheres are not added. The preparation method thereof comprises the following steps: heating paraffin to 60°C, stirring at 400 r / min for 60 min, adding heat-expandable microspheres, stirring at 800 r / min at 70°C for 20 min, cooling to room temperature, and crushing; the amount of paraffin added is 30% of the mass of the heat-expandable microspheres.

[0045] Preparation Example 2.6 The modified microsphere filler is different from Preparation Example 2.1 in that no heat-expandable microspheres are added. Its preparation method comprises the following steps: heating paraffin to 60°C, stirring at 400 r / min for 60 min, adding ceramic microspheres, stirring at 800 r / min at 70°C for 20 min, cooling to room temperature, and crushing; the amount of paraffin added is 30% of the total mass of the ceramic microspheres. Example

[0046] Example 1 A large-particle recycled aggregate concrete, wherein the raw materials and the amounts of the raw materials are shown in Table 1, wherein the self-repairing filler comprises a modified fiber filler and a modified microsphere filler in a mass ratio of 1:2, the modified fiber filler is prepared by Preparation Example 1.1, and the modified microsphere filler is prepared by Preparation Example 2.1; the water reducer is a polycarboxylic acid-based water reducer; the floating beads are a cellulose ester with an apparent density of 0.6×10 3 kg / m 3 Fly ash spherical floating beads.

[0047] Table 1 Example 1 Example 2 Example 3 Example 4 Recycled coarse aggregate / Kg 800 700 950 750 Fine aggregate / Kg 650 650 500 600 Cement / Kg 300 400 350 400 Fly ash / Kg 40 60 40 50 Mineral powder / Kg 50 60 60 40 Self-repairing filler / Kg 70 60 80 60 Water reducing agent / Kg 25 20 30 25 Silane coupling agent / Kg 4 3 5 8 Floating beads / Kg 80 60 70 70 Water / Kg 200 150 250 200 The method for preparing the above-mentioned large-particle recycled aggregate concrete comprises the following steps: S1: Mix and stir recycled coarse aggregate, fine aggregate, cement, fly ash and floating beads for 1 hour to prepare a primary mixture; S2: Mixing the modified microsphere filler and the modified fiber filler to obtain a self-repairing filler; S3: Add the initial mixture into water, add the silane coupling agent, mix and stir for 30 minutes, then add the modified microsphere filler, and continue stirring for 20 minutes.

[0048] Example 2 A large-particle recycled aggregate concrete, which is different from Example 1 in that the raw materials and the amounts of the raw materials are shown in Table 1, wherein the self-repairing filler comprises a modified fiber filler and a modified microsphere filler in a mass ratio of 3:4, the modified fiber filler is prepared by Preparation Example 1.2, and the modified microsphere filler is prepared by Preparation Example 2.2; the floating beads have an apparent density of 0.8×10 3 kg / m 3 The fly ash spherical floating beads are prepared, and the other steps are the same as those in Example 1.

[0049] Example 3 A large-particle recycled aggregate concrete is different from Example 1 in that the raw materials and the amounts of the raw materials are shown in Table 1, wherein the self-healing filler includes a modified fiber filler and a modified microsphere filler in a mass ratio of 4:5, the modified fiber filler is prepared by Preparation Example 1.3, and the modified microsphere filler is prepared by Preparation Example 2.3, and the other steps are the same as those in Example 1.

[0050] Example 4 A large-particle recycled aggregate concrete is different from Example 1 in that the raw materials and the amounts of the raw materials are shown in Table 1, wherein the self-healing filler includes a modified fiber filler and a modified microsphere filler in a mass ratio of 4:3, the modified fiber filler is prepared by Preparation Example 1.1, and the modified microsphere filler is prepared by Preparation Example 2.3, and the other steps are the same as those in Example 1.

[0051] Embodiment 5-7 A large-particle recycled aggregate concrete, which is different from Example 1 in that the source of the modified fiber filler in the self-repairing filler is shown in Table 2, and the other steps are the same as Example 1.

[0052] Table 2 Group Sources of Modified Fiber Fillers Example 5 Preparation Example 1.4 Example 6 Preparation Example 1.5 Example 7 Preparation Example 1.6 Examples 8-10 A large-particle recycled aggregate concrete, which is different from Example 1 in that the source of the modified microsphere filler in the self-repairing filler is shown in Table 3, and the other steps are the same as Example 1.

[0053] Table 3 Group Sources of Modified Fiber Fillers Example 8 Preparation Example 2.4 Example 9 Preparation Example 2.5 Example 10 Preparation Example 2.6 Comparative Example Comparative Example 1 A large-particle recycled aggregate concrete is different from Example 1 in that no modified fiber filler is added to the self-repairing filler, the modified fiber filler is replaced by a modified microsphere filler of equal mass, and other steps are the same as Example 1.

[0054] Comparative Example 2 A large-particle recycled aggregate concrete is different from Example 1 in that no modified microsphere filler is added to the self-repairing filler, the modified fiber filler is replaced by a modified fiber filler of equal mass, and the other steps are the same as Example 1.

[0055] Comparative Example 3 A large-particle recycled aggregate concrete is different from Example 1 in that no self-repairing filler is used in the raw materials, the modified fiber filler is replaced by fine aggregate of equal mass, and the other steps are the same as Example 1.

[0056] Comparative Example 4 A recycled concrete and a preparation method thereof, comprising the following steps: S1: Preparation of admixture KN1: 0.5Kg of hyperbranched anti-mud polycarboxylic acid component PC1, 0.005Kg of foam control component (Wacker silicone defoamer), 0.01Kg of early strength component (diethanol monoisopropanolamine) and 1Kg of water are mixed evenly; wherein the preparation method of the hyperbranched anti-mud polycarboxylic acid component PC1 comprises the following steps: 1Kg of octadecyl diethanolamine and 0.3Kg of methyl acrylate are added to the first reactor, and 0.002Kg of tetraalkyl titanate and 0.008Kg of phenothiazine are added, and an ester exchange reaction is carried out at 150°C and 10kPa pressure for 8h, and the ester exchange product is collected; 1Kg of the obtained ester exchange product and 5Kg of anhydrous ethanol are added to the second reactor, and 2Kg of alkylating agent methyl chloride is introduced to carry out quaternization reaction at 40°C and 150kPa pressure for 4h to obtain the hyperbranched cationic Monomer; wherein, methyl chloride is introduced into the second reactor in 5 times, and the remaining methyl chloride is blown off with nitrogen after the reaction is completed, and the temperature in the second reactor is raised to 120° C. to evaporate the solvent anhydrous ethanol to obtain a hyperbranched cationic monomer; 100 kg of isopentanol polyoxyethylene ether (molecular weight 2400) is added to the reaction container and dissolved in water, and then 3 kg of hyperbranched cationic monomer and 0.8 kg of ammonium persulfate are added, and the temperature is raised to 50° C., and an aqueous solution containing 4 kg of acrylic acid and 2 kg of hydroxyethyl acrylate is uniformly added dropwise, and an aqueous solution containing 0.4 kg of ascorbic acid and 0.6 kg of mercaptopropionic acid is added dropwise at the same time, and the dropping time of the two solutions is 180 min and 200 min respectively. After the dropping is completed, the temperature is kept for 90 min, and a NaOH solution is added to adjust the solution pH to 5.4; the solid content of the obtained hyperbranched anti-mud type polycarboxylic acid component is 39%; S2: 580 kg of recycled coarse aggregate, 1.2 kg of sodium silicate and 0.32 kg of admixture KN1 are placed in a stirring pot and mixed evenly, and stirred until the aggregate is saturated and surface dry to obtain pretreated recycled aggregate; S3: Add 400 kg of crushed stone and 870 kg of regenerated sand, mix evenly with the pre-treated regenerated coarse aggregate to obtain mixed aggregate; S4: Add 60 kg fly ash and 300 kg Portland cement, and mix well with the mixed aggregate; S5: Add 1.28 kg of admixture KN1 and 180 kg of water, stir evenly to obtain recycled concrete.

[0057] Performance testing The concrete specimens prepared in Examples 1-10 and Comparative Examples 1-4 were tested for compressive strength, impermeability and crack resistance. Each test was divided into three groups, and the average value of the three groups of test results was taken as the final result and recorded in Table 4.

[0058] Compressive strength: standard test blocks were prepared according to GB / T 50081-2016 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the compressive strength of the standard test blocks was measured after curing for 7 days and 28 days; Anti-seepage performance: 1. According to the provisions of GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the water seepage height method was used to test the water permeability of the prepared concrete. The curing age was 28 days. A truncated cone with a diameter of 175 mm, an inner diameter of 185 mm at the lower mouth and a height of 150 mm was used for the test. A rubber sealing ring was used as the sealing material. The specimen was taken out 24 hours before reaching the test age. The specimen was sealed with a rubber sealing ring. According to the specification, 1.2±0.05 MPa was selected as the constant water pressure within 24 hours. A concrete impermeability tester was used as the test instrument to determine the average water seepage height of different impermeable concretes under constant water pressure. 2. The chloride ion penetration resistance test was carried out according to the RCM method in GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", and the average chloride ion diffusion coefficient D of the three samples was calculated. RCM ; The early crack resistance test was carried out in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete".

[0059] Table 4 According to the performance test results in Table 4, it can be seen that the large-particle recycled aggregate concrete of the present application has higher tensile strength and better impermeability, overcoming the shortcomings of poor impermeability and poor crack resistance of concrete prepared by obtaining recycled coarse aggregate from waste concrete.

[0060] According to the performance test results of Examples 1-4 and Comparative Examples 3-4, it can be seen that by adding modified fiber fillers and modified microsphere fillers to the concrete raw materials, the fiber network structure formed by the modified fiber fillers cooperates with the modified microsphere fillers to promote the formation of aggregate interlocking effect of recycled coarse aggregate inside the concrete, fill the pores and microcracks generated by the waste concrete through crushing and screening processes, reduce the porosity of the concrete, improve the interface transition zone between the recycled aggregate and the cement slurry, reduce the interface pores and defects, effectively improve the water permeability, chloride ion penetration resistance and crack resistance of the prepared concrete, and improve the durability of the concrete.

[0061] According to the performance test results of Examples 1-4, Examples 5-7 and Comparative Example 1, it can be seen that the synergistic effect of basalt fiber and polyvinyl alcohol fiber is more significant than the outstanding contribution of using only a single fiber to the impermeability and crack resistance of concrete. Spraying ethyl cellulose solution and phosphatidylserine solution on the fiber surface can effectively improve the crack resistance of the modified fiber filler and further improve the impermeability of concrete.

[0062] As a kind of rigid fiber, basalt fiber shows a more advantageous effect in improving the compressive strength of concrete. As a flexible fiber, polyvinyl alcohol fiber has better flexibility and can more effectively penetrate into the gaps between aggregates to fill them, showing a more effective effect in enhancing the impermeability of concrete. The two work together to improve the fiber network structure formed by the modified filler fiber for filling the internal gaps and cracks of concrete, while improving the compressive strength and crack resistance of concrete and the durability of concrete.

[0063] According to the performance test results of Examples 1-4, Examples 8-10 and Comparative Example 2, it can be seen that the mixed use of thermal expansion microspheres and ceramic microspheres shows a more prominent effect on the impermeability and crack resistance of concrete. The modified microsphere filler modified by paraffin wax wrapping has higher diffusivity and adhesion, can be evenly dispersed in the concrete raw material, promotes the filling of microspheres into the pores in the concrete, further improves the impermeability, and makes the concrete prepared with waste concrete as raw material have better durability.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A large-particle recycled aggregate concrete, characterized in that: The raw materials include, by weight: 700-950 parts of recycled coarse aggregate, 500-650 parts of fine aggregate, 300-400 parts of cement, 40-60 parts of fly ash, 40-60 parts of mineral powder, 60-80 parts of self-repairing filler, 20-30 parts of water reducer, 3-8 parts of silane coupling agent, 60-80 parts of floating beads and 150-250 parts of water; The self-repairing filler comprises a modified fiber filler and a modified microsphere filler in a mass ratio of (1-4):(2-6).

2. The large-particle recycled aggregate concrete according to claim 1, characterized in that: The modified fiber filler comprises basalt fiber and polyvinyl alcohol fiber in a mass ratio of (2-8):(1-4).

3. The large-particle recycled aggregate concrete according to claim 2, characterized in that: The preparation method of the modified fiber filler comprises the following steps: The basalt fiber and the polyvinyl alcohol fiber are mixed in proportion to obtain mixed fibers; The ethyl cellulose solution is evenly sprayed on the surface of the mixed fiber, and then the phosphatidylserine solution is evenly sprayed, and the mixture is dried and dispersed until there is no mutual adhesion between the basalt fiber and the polyvinyl alcohol fiber.

4. The large-particle recycled aggregate concrete according to claim 1, characterized in that: The modified microsphere filler comprises thermal expansion microspheres and ceramic microspheres in a mass ratio of (2-5):

1.

5. The large-particle recycled aggregate concrete according to claim 4, characterized in that: The preparation method of the modified microsphere filler comprises the following steps: Heat paraffin to 60-70°C, stir at 400-500r / min for 30-60min, add heat-expandable microspheres and ceramic microspheres, stir at 800-900r / min at 60-70°C for 20-30min, cool to room temperature and crush to obtain the product; the amount of paraffin added is 30-40% of the total mass of the heat-expandable microspheres and the ceramic microspheres.

6. The large-particle recycled aggregate concrete according to claim 1, characterized in that: The recycled coarse aggregate is 10-20 mm continuously graded coarse aggregate obtained after crushing and screening of waste concrete, and its crushing value is 12-20%; the fine aggregate is sand with a fineness modulus of 2.6-3.2; the fly ash is Class F Grade I fly ash, and the mineral powder is Grade S95 mineral powder.

7. The large-particle recycled aggregate concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.

8. The large-particle recycled aggregate concrete according to claim 1, characterized in that: The floating beads have an apparent density of 0.6×10 3 kg / m 3 -0.8×10 3 kg / m 3 Fly ash spherical floating beads.

9. The method for preparing large-particle recycled aggregate concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: The recycled coarse aggregate, fine aggregate, cement, fly ash and floating beads are mixed to prepare a primary mixture; The modified microsphere filler and the modified fiber filler are mixed to prepare the self-repairing filler; Add the primary mixture into water, add the silane coupling agent, add the modified microsphere filler after mixing, and stir to obtain the product.

Citation Information

Patent Citations

  • Silane coupling agent-fly ash floating bead light-weight high-intensity foam concrete and preparation method thereof

    CN107602018A

  • High-strength recycled concrete and preparation method thereof

    CN110526610A

  • Recycled large aggregate concrete capable of being mixed and poured and preparation method thereof

    CN111499297A

  • Recycled aggregate concrete and preparation method thereof

    CN112374832A

  • Recycled aggregate concrete and preparation method thereof

    CN112811866A